Kedudukan Hak Waris Anak Luar Kawin Menurut Hukum Adat di Desa Langkuru, Kecamatan Pureman, Kabupaten Alor, Nusa Tenggara Timur - Nimrot Frare; Luh Ketut Ayu Manik Sastrini; Ni Made Witari Dewi (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2025)
In the community of Langkuru Village, Pureman District, Alor Regency, there are often illegitimate children who cause problems because they become a topic of discussion in the community. The process of resolving illegitimate children can be carried out with national law or through customary law as is done by the community of Langkuru Village, East Nusa Tenggara (NTT). The settlement of illegitimate children according to customary law in Langkuru Village, Pureman District, Alor Regency, East Nusa Tenggara, is usually resolved in the Customary Warehouse (langwah) because the Customary Warehouse (langwah) is a place of peace for customary problems and never has to get a court decision because basically the residents of Langkuru Village can resolve it by mutual agreement, either a joint agreement with the family or a joint agreement according to custom. The position of illegitimate children in the distribution of inheritance in Langkuru Village remains the same as the distribution of inheritance against legitimate because it adheres to the matrilineal customary system. This type of research uses an empirical legal research type with a sociological legal approach and primary data sources and secondary data are then analyzed descriptively qualitatively.